A-Flow: managing dataflows on the computing continuum using abstract communication channels - Torres-Charles, Catherine; Sanchez-Gallegos, Dante D.; Carrizales-Espinoza, Diana; Gonzalez-Compean, J. L.; Carretero, Jesus (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2025: Anais do XXXVII International Symposium on Computer Architecture and High Performance Computing, 2025)
Computing continuum systems are emerging as a solution for organizations to process data across diverse infrastructures, reducing latency compared to traditional cloud computing. However, managing I/O operations in such distributed and heterogeneous environments remains an open research challenge. In this paper, we present A-Flow, a model for constructing I/O systems to manage data exchange in computing continuum environments. These systems are built around data distribution patterns defined by structures called abstract communication channels (ACCs). ACCs are established between processing stages using memory, file system, and network resource connections. To prevent resource overload during execution, A-Flow automatically selects the appropriate communication channel based on user-defined criteria such as throughput or resource utilization. We implemented this model in a prototype and evaluated it through a case study focused on managing medical data in HDF5 format across different environments. The evaluation revealed that A-Flow’s ACCs can be integrated into existing stage-based systems found in the state of the art. The results highlight the efficiency and effectiveness of A-Flow in enabling dataflows across heterogeneous infrastructures, addressing key challenges in computing continuum.